Data Warehouse Design and Build Data Warehouse Using Ontology and Rule Base Method in Supporting Sales and Service Information - Qusyairi, Muhammad (International Journal of Engineering and Emerging Technology, 2020)
Data warehouse makes company data that is spread out become integrated and concise so that it helps managers or top management in analyzing existing data for strategic and fast decision making. With the application of data warehouses using the rule base ontology method, it makes the class of related data relations easier to analyze so that it helps companies monitor the good results of sales data relating to goods, sales locations, turnover values, and data services related to product service, region , technician, and service value